2020
DOI: 10.21203/rs.3.rs-31840/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humic-acid-driven escape from eye parasites revealed by RNA-seq and target-specific metabarcoding

Abstract: Background Next generation sequencing (NGS) technologies are extensively used to dissect the molecular mechanisms of host-parasite interactions in human pathogens. However, ecological studies have yet to fully exploit the power of NGS as a rich source for formulating and testing new hypotheses. Methods We studied Eurasian perch (Perca fluviatilis) and its eye parasite (Trematoda, Diplostomidae) communities in fourteen lakes that differed in humic content in order to explore host-parasite-environment interactio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…As such, these findings contrast recent reports in three‐spine stickleback (Marques et al, 2017) and Baltic herring (Hill et al, 2019), where a single amino acid change was shown to have a major effect on ecological adaptation. Nevertheless, recent work based on RNA‐sequencing analysis of the whole eye in Eurasian perch has shown differential expression of visual red‐, green‐ and short‐wavelength‐sensitive opsins ( OPN1LW / opn1lw1 , OPN1MW / opn1mw1 and OPN1SW / opn1sw2 , respectively) between humic and clear‐water environments (Noreikiene et al, 2020), indicating that regulation of visual opsin expression still occurs in humic lakes and may represent an important mechanism of adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, these findings contrast recent reports in three‐spine stickleback (Marques et al, 2017) and Baltic herring (Hill et al, 2019), where a single amino acid change was shown to have a major effect on ecological adaptation. Nevertheless, recent work based on RNA‐sequencing analysis of the whole eye in Eurasian perch has shown differential expression of visual red‐, green‐ and short‐wavelength‐sensitive opsins ( OPN1LW / opn1lw1 , OPN1MW / opn1mw1 and OPN1SW / opn1sw2 , respectively) between humic and clear‐water environments (Noreikiene et al, 2020), indicating that regulation of visual opsin expression still occurs in humic lakes and may represent an important mechanism of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, increased DOC can also limit whole‐lake primary production and underwater higher vegetation, supporting the microbial loop and influencing resource availability and quality for consumers (Ask et al, 2009; Cole, 2009; Karlsson et al, 2009). Thus, DOC influences whole lake food‐webs from primary producers to top predators and parasites (Grether et al, 2001; Tobler & Path, 2011; Kaeuffer et al, 2012; Noreikiene et al, 2020).…”
Section: Introductionmentioning
confidence: 99%